Using judgments in second language acquisition research - Spinner, Patti 1973-; Gass, Susan M. (Routledge, 2019)
Synthesizing the theory behind and methodology for conducting judgment tests, Using Judgments in Second Language Acquisition Research aims to clarify the issues surrounding this method and to provide best practices in its use. The text is grounded on a balanced and comprehensive background of the usage of judgment data in the past up through its present-day applications. SLA researchers and graduate students will find useful a chapter serving as a "how-to" guide for a variety of situations to conduct research using judgments, including ways to optimize task design and examples from successful studies. Lucid and practical, Using Judgments in Second Language Acquisition Research offers guidance on a method widely used by SLA researchers, both old and new to the field
Keywords: Second language acquisition / Research / Methodology